On the benefits of consumer IT in the workplace—An IT empowerment perspective. (June 2022) - Junglas, Iris; Goel, Lakshmi; Rehm, Sven-V.; Ives, Blake
Abstract: Technology driven organizational transformation—heightened during the COVID-19 pandemic—is gaining momentum, as employees increasingly invest in technology for work. Referred to as IT consumerization, employees use their smartphones, notebooks and tablets in the workplace, accompanied by a growing toolbox of applications. Google Apps and Dropbox are just a few consumer tools that employees use to get their work done, and in doing so, often bypass the authority of the IT department and the organization. While some organizations discourage, or even prohibit, employees from using their personal IT, others embrace the phenomenon. Employees' investment in consumer IT and its accompanying applications has been suggested as related to innovation and productivity gains, but there has been no empirical validation of such a beneficial relationship. With this paper we propose a theoretical root cause for the perceived positive outcomes of employees using their personal technologies in the workplace. Specifically, we explore the role of IT empowerment—a concept that captures the level of authority an employee assumes in utilizing IT in order to control or improve aspects of their job. Surveying 147 employees, we find support for increased levels of IT empowerment and higher levels of perceived performance among those that actively use consumer IT versus those that do not; we also find a close relationship between IT empowerment and perceived innovative work behaviors. Highlights: The use of consumer devices and applications in the workplace is ever more prevalent. IT consumerization may be explained by the psychological concept of IT empowerment. IT empowerment is positively related to perceived productivity. IT empowerment is positively related to perceived innovative work behaviors. IT empowerment is a concept that IT innovation researchers should pay attention to.